PENGARUH SELFT REGULATED LEARNING DAN LITERASI DIGITAL TERHADAP MOTIVASI BERPRESTASI SISWA - Yowelna Tarumasely (IAKN Ambon, 2020)
The context of learning during the Covid-19 emergency requires learning to be carried out from home or distance learning. Distance learning requires students to be able to manage their own learning, in addition, digital literacy is needed for students to be able to access the learning process and information and select the information needed. The ability to organize them in learning and good digital literacy will increase student achievement motivation. This study aims to determine: 1) The Effect of Self- Regulated Learning on Achievement Motivation of Class VII Students of SMP Negeri 9 Ambon in the Distance Learning System, 2) The Effect of Digital Literacy Ability on Achievement Motivation of Class VII Students of SMP Negeri 9 Ambon in Distance Learning System 3) The Influence of Self-Regulated Learning and Digital Literacy Ability on Achievement Motivation of Class VII Students of SMP Negeri 9 Ambon in Distance Learning Systems. The method used is a quantitative method. The data analysis technique used is multiple linear regression analysis. Data processing used the SPSS version 21 program. The results show that: 1) there is an effect of self-regulated learning on achievement motivation, 2) there is an effect of digital literacy on student achievement motivation, and 3) there is an effect of simultaneous self-regulated learning and digital literacy towards the students’motivation of SMP Negeri 9 in distance learning system.